Wielkie serce : korespondencja Kornela Ujejskiego z rodzina Mlodnickich - Ujejski, Kornel, 1823-1897.; Mlodnicka, Wanda, d. 1923.; Sudolski, Zbigniew (Warszawa : Ancher, 1992)
The correspondence of a famous Polish poet with the Mlodnicki family.
Errata leaf ([2] p.) at the end of v. 2.
Includes bibliographical references and index.
Keywords: Ujejski, Kornel, -- 1823-1897 -- Correspondence; Mlodnicka, Wanda, -- d. 1923 -- Correspondence; Mlodnicki family; Poets, Polish -- 19th century -- Correspondence